AMBIVALENT AND NOSTALGIC ATMOSPHERE IN KIRAN DESAI’S THE INHERITANCE OF LOSS - Kumar, Susheel (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kiran Desai’s The Inheritance of Loss is considered to be the best postcolonial novel, having multiple geographic settings as a backdrop, cross-cultural diasporic identities, multi-layered narration and representations, cultural conflicts, and deviations from moral values and ethics of the East and the West inextricably interlinked under the impact of ambivalence and nostalgia in her fictional Kalimpong town located in the western part of Darjeeling Hills in the Eastern Himalayas of India, where the local, colonial, postcolonial and global live, long and belong.